(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The study was carried out in the village of Bustan Al-Hamam in the city of Baniyas during the year 2023 on apricot trees of my variety grafted on seed stock. The experiment was carried out with 9 treatments and each treatment with three replicates. The aim of the research was “to study the effect of foliar feeding with the organic fertilizer “Natur” and the marine algae extract “Gatun.” In improving the leaf content of chlorophyll and the quality and hardness of the fruits of the local apricot variety, the results showed the following: The parameter was given (algaton 2.5 ml/l+ nator 2 ml/l) the highest background of the total Clovel (44.31spad). As a result of the statistical analysis, they outperformed all the different coefficients. In terms of fruit quality, it emerged as a distinguished candidate (algaton 2.5 ml/l+ nator 2 ml/l) in the juice content of soluble solids in the studio (19.40%), and it also excelled in excellence (algaton 2.5 ml/+ nator 2 ml/l) in the field of juice in terms of total sugars for Bulgaria (17.30%). Its efficiency exceeded the comprehensive fruits (algaton 2.5 ml/+ nator 1.5 ml/l ) in terms of its overall fruit efficiency (0.0466% ) compared to the control that achieved the least solidity of the overall profit (0.1% ).in terms of fruit hardness,the treatment was surperior (algaton 2.5 ml/+ nator 2 ml/l) in terms of fruit hardness with a value of (3.650) compared to the control, which achieved the lowest fruit hardness with a value of (1.397kg). Accordingly, proper feeding with fertilizers and marine algae extracts can be used to improve the chlorophyll content of the leaves and improve the quality of the fruit.